SOCIAL CONSOLIDATION AND EDUCATION - O.V. Mateiyenko (Academy of Cognitive and Natural Sciences, 2004)
The article deals with certain educational problems of nowadays European community: the mice of the illiterate, the expulsion of pupils from schools, inadequate level graduates. Special attention is given to minimal standards and different levels of command in education.